Smart Sensor Node Design with Energy Harvesting for Industrial IoT Applications - S. M Pavalam; M. Babylatha (National Journal of Electrical Electronics and Automation Technologies, 2025)
Industrial Internet of Things (IIoT) is also becoming an Industry 4.0 paradigm that focuses on monitoring, control, and optimization of industrial processes and company logistics in real-time as monitored by distributed intelligent sensor nets. Nevertheless, installation of the conventional battery-powered sensor nodes in industrial environments, which are harsh and sometimes inaccessible, can pose considerable problems because of short lifetimes of operation, high maintenance, and downtime costs of changing the batteries. To curb these drawbacks, the paper lists a design and development of self-powered IoT architecture of smart sensor node to encapsulate multi-source energy harvesting mechanisms (sun, vibration, and thermal) combined with a smart power management unit, which provides power efficient utilization. The hybrid energy storage model integrated in the system consists of a supercapacitor which enables ultra-fast energy buffering and a rechargeable lithium-ion battery to store energy over time, thus the system can continue to operate without failure irrespective of the changing environmental factors. An industrial grade temperature, pressure and vibration sensor with onboard signal conditioning is used and data is processed by an ultra-low-power ARM Cortex-M4 microcontroller capable of edge-level anomaly detection to reduce communication overheads. The LoRaWAN specification supports long-range, low-power wireless communications, and has adaptive transmission power control to ensure that the transmission efficiency works as efficiently as possible in order to guarantee reliable network connectivity in a changing interference environment typical of industrial environments. The sensing, processing, and transmission occurrances are dynamically scheduled using an energy-aware duty cycling algorithm that adapts to the energy level that is harvested to extend the lifetime of the operations. This architecture was confirmed by simulations, and physical prototype testing in an industrial setting where it delivered a 62 percent increase in the energy autonomy and a 47 percent decrease in the total power consumption compared to industrial battery-powered systems. These findings validate that the proposed smart sensor node will be a viable, sustainable and none maintenance solution to IIoT applications requiring predictive maintenance, asset tracking and environmental monitoring, with long-term deployment-options with no performances and reliability hindrance.